ANALISIS PROFITABILITAS KERIPIK SINGKONG PADA INDUSTRI RUMAH TANGGA PASUNDAN DI KOTA PALU - Patoki, Alto Kristian; Effendy, Effendy (AGROTEKBIS, 2017)
The study aims to determine the amount of revenue and profitability of the business value of cassava chips in the industry "Pasundan" in the city of Palu. The research was conducted on a month from November to December 2015. The number of respondents as many as four people. The analysis tool used is the analysis of revenue and profitability analysis. The results showed that the amount of revenue earned processed cassava chips business on domestic industry "Pasundan" during November-December 2015 amounted to Rp 17.856.592with an average of Rp8.928.296. Profitability average value obtained domestic Industry "Pasundan" of November-December 2015 through computation ROI of 89,39% means that the value of profitability shows that the company earned a net profit of invested capital which is equal to 89,39% per month in restore assets owned domestic industry "Pasundan".Â Keywords: Cassava Chips, Pasundan Industry, Profitability